2009
DOI: 10.4314/eamj.v77i11.46735
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative colonic irrigation in the management of left sided large bowel emergecies in Jos University Teaching Hospital, Nigeria

Abstract: Objectives: To evaluate the safety and benefits of antegrade intraoperative colonic irrigation (lavage) and primary anastomosis, after colonic resection, in the treatment of left sided large bowel emergencies. Design: A prospective descriptive study. Setting: Jos University Teaching Hospital, Jos, Nigeria. Participants: Thirty seven patients with an average age of 44.86 ± 16.15 years. Intervention: Sigmoid colectomy was performed in twenty two sigmoid volvulus, five sigmoid cancer, two faecal fistulae and one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…3,4 In treating SCV, emergency operation is needed in cases of unsuccessful nonoperative treatment and when bowel gangrene or peritonitis is present. [1][2][3][4][5][6][7][8][17][18][19][20][21][22][23] We generally prefer a standard midline incision, as do some other surgeons, 8 which allows for all therapeutic procedures, such as detorsion, pexy, resection, anastomosis, or stomas. The basic principles of surgery are releasing the torsion, ascertaining the procedure to be performed (the first priority is to save life and the second is to obviate the possibility of recurrence), and treating complications if they arise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 In treating SCV, emergency operation is needed in cases of unsuccessful nonoperative treatment and when bowel gangrene or peritonitis is present. [1][2][3][4][5][6][7][8][17][18][19][20][21][22][23] We generally prefer a standard midline incision, as do some other surgeons, 8 which allows for all therapeutic procedures, such as detorsion, pexy, resection, anastomosis, or stomas. The basic principles of surgery are releasing the torsion, ascertaining the procedure to be performed (the first priority is to save life and the second is to obviate the possibility of recurrence), and treating complications if they arise.…”
Section: Discussionmentioning
confidence: 99%
“…Operative cleansing may be added to perform the primary anastomosis with reasonable safety. 3,21 Otherwise, Hartmann_s or Mikulicz procedures with resection may be lifesaving in gangrenous or unstable patients. However, they carry the mortality and morbidity risks of stomas and require a second operation.…”
Section: Discussionmentioning
confidence: 99%
“…The only report in which some patients (12%) had low stapled anastomosis of rectal carcinoma came from Lagos where a few patients could afford to procure the instruments (Adesanya 2006). The patients who presented with intestinal obstruction had emergency resections with end‐to‐end anastomosis (as one‐stage procedures) in some institutions (Sule et al . 2000) while others had preliminary colostomies (Akute 2000).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies on sigmoid volvulus explored the feasibility of one-stage resection using on-table lavage [13,[21][22][23][24] . The advantages of this approach include single stage procedure, no need for a colostomy, possible lower morbidity and mortality, and shorter hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, obstruction of the left colon is managed by a multi-stage defunctioning colostomy and resection. However, there is a growing acceptance of one-stage primary resection and anastomosis with the use of on-table antegrade irrigation [24,[26][27][28] . However, several studies have suggested that on-table lavage may not be necessary for a safe emergency RPA of unprepared left colon [26][27][28][29] .…”
Section: Discussionmentioning
confidence: 99%